Meta-analysis of chemotherapy in head and neck cancer (MACH-NC): An update on 107 randomized trials and 19, 805 patients, on behalf of MACH-NC Group. (March 2021) - Lacas, Benjamin; Carmel, Alexandra; Landais, Cécile; Wong, Stuart J.; Licitra, Lisa; Tobias, Jeffrey S.; Burtness, Barbara; Ghi, Maria Grazia; Cohen, Ezra E.W.; Grau, Cai; Wolf, Gregory; Hitt, Ricardo; et al.
Highlights: MACH-NC second update with 107 randomized trials (19805 patients) investigating chemotherapy (CT) in non-metastatic HNSCC. Overall Survival (OS) improved by CT, benefit superior for concomitant CT (HR 0.83 [0.79; 0.86]) over induction or adjuvant CT. Direct comparison confirmed the superiority of concomitant over induction CT on OS. Abstract: Background and purpose: The Meta-Analysis of Chemotherapy in squamous cell Head and Neck Cancer (MACH-NC) demonstrated that concomitant chemotherapy (CT) improved overall survival (OS) in patients without distant metastasis. We report the updated results. Materials and methods: Published or unpublished randomized trials including patients with non-metastatic carcinoma randomized between 1965 and 2016 and comparing curative loco-regional treatment (LRT) to LRT + CT or adding another timing of CT to LRT + CT (main question), or comparing induction CT + radiotherapy to radiotherapy + concomitant (or alternating) CT (secondary question) were eligible. Individual patient data were collected and combined using a fixed-effect model. OS was the main endpoint. Results: For the main question, 101 trials (18951 patients, median follow-up of 6.5 years) were analyzed. For both questions, there were 16 new (2767 patients) and 11 updated trials. Around 90% of the patients had stage III or IV disease. Interaction between treatment effect on OS and the timing of CT was significant ( p < 0.0001), the benefit being limited to concomitant CT (HR: 0.83, 95%CI [0.79; 0.86]; 5(10)-year absolute benefit of 6.5% (3.6%)). Efficacy decreased as patients age increased (p_trend = 0.03). OS was not increased by the addition of induction (HR = 0.96 [0.90; 1.01]) or adjuvant CT (1.02 [0.92; 1.13]). Efficacy of induction CT decreased with poorer performance status (p_trend = 0.03). For the secondary question, eight trials (1214 patients) confirmed the superiority of concomitant CT on OS (HR = 0.84 [0.74; 0.95], p = 0.005). Conclusion: The update of MACH-NC confirms the benefit and superiority of the addition of concomitant CT for non-metastatic head and neck cancer.